2007
DOI: 10.1080/09638280600960909
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality in stroke rehabilitation: Still more virtual than real

Abstract: VR is a potentially exciting and safe tool for stroke rehabilitation but its evidence base is too limited by design and power issues to permit a definitive assessment of its value. Thus, while the findings of this review are generally positive, the level of evidence is still weak to moderate, in terms of research quality. Further study in the form of rigorous controlled studies is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 32 publications
3
108
0
4
Order By: Relevance
“…In clinics, static balance ability and postural sway are usually measured using a force plate (Era et al 2002;Sihvonen et al 2004), whereas BBS and TUG are used to evaluate dynamic balance ability. Virtual reality training has been used in previous studies and has shown to improve walking (Crosbie et al 2007) and upper extremity function (Saposnik et al 2010a(Saposnik et al , 2010b in stroke patients.…”
Section: Disscussionmentioning
confidence: 99%
“…In clinics, static balance ability and postural sway are usually measured using a force plate (Era et al 2002;Sihvonen et al 2004), whereas BBS and TUG are used to evaluate dynamic balance ability. Virtual reality training has been used in previous studies and has shown to improve walking (Crosbie et al 2007) and upper extremity function (Saposnik et al 2010a(Saposnik et al , 2010b in stroke patients.…”
Section: Disscussionmentioning
confidence: 99%
“…Evidence on effectiveness was considered crucial for decisions on further implementation. We found these recommendations in the following reviews: virtual reality (VR) in stroke rehabilitation [29]; Internet administered Cognitive Behavioral Therapy (eCBT ) [30]; e-Therapy [31]; and electronic decision support systems [32]. A review on technologies for an aging society pointed out the need for evidence not only for clinical, but also technical, ethical, legal, economical and organisational effects [33].…”
Section: More Summative Studies With Larger Samples Preferably Rctsmentioning
confidence: 99%
“…Balance training with Nintendo ® Wii Fit and Nintendo ® Wii Balance Board is a virtual realitybased technology that simulates real-life learning of an activity and allows increasing training intensity, giving a 3D feedback by means of visual, sensory and auditory stimulation. This technology allows users to interact with a computer-generated scenario in a virtual world, making corrections while an activity is underway (6).…”
Section: Resultsmentioning
confidence: 99%